Importance of Public Relations and its Tools in the Hospitality Industry - Mr. Parikshit Singh Tanwar; Dr Rubaid Ashfaq (Journal of Social Responsibility, Tourism and Hospitality, 2023)
The topic of the study is the Importance of public relations and its tools in the hospitality industry. The study's goals included analyzing the purposes and goals of public relations in hotels, learning how hotels use PR tools and techniques, and looking at how hotels use corporate reputation and trust. The study's mixed methodology shows that an analysis was conducted that was both qualitative and quantitative in character. The research found that public relations were "settled" at the hotel, which had a Public Relations Unit inside the Marketing Department and well-stated aims and objectives. However, based on the feedback provided by the hotel's customers, it is crucial for the establishment to regularly gauge the opinions of its stakeholders or actively involve its clientele, as recommended by public relations theories. The study concluded that effective PR techniques have a favorable effect on hotels' corporate reputations, growth, and goodwill.